External control, corporate strategy, and firm performance in research‐intensive industries - Hill, Charles W. L.; Snell, Scott A. (Strategic Management Journal, 1988)
Abstract This paper explores the proposition that the divergence of interest between managers and stockholders has implications for corporate strategy and firm profitability. Stockholders prefer strategies which maximize their wealth. Managers prefer strategies which maximize their utility. It is theorized that in research‐intensive industries, when stockholders dominate, innovation strategies are favored. When managers dominate, diversification strategies are favored. In addition, innovation is argued to be associated with greater firm profitability than diversification. This theory is tested on 94 Fortune 500 firms drawn from research‐intensive industries. The results largely confirm theoretical expectations.